A new species of gecko from arid inland regions of eastern Australia (Diplodactylus; Diplodactylidae) - Couper, Patrick J.; Oliver, Paul M. (Zootaxa, 2016)
We describe a new species of small terrestrial gecko in the genus Diplodactylus from inland regions of western Queensland and New South Wales, Australia. Diplodactylus ameyi sp. nov. can be distinguished from its congeners in the Diplodactylus conspicillatus species-group by its relatively large size, bulbous tail which lacks an acute attenuated extension at tip, small first labial scale and comparatively robust head morphology (which includes a broadly rounded snout and no well-defined canthus rostralis). Related populations from eastern and central Queensland currently referred to D. platyurus include further deeply divergent lineages but additional material is required to resolve systematic boundaries in this region.